A post-quantum light weight 1-out-n oblivious transfer protocol. (May 2019) - Mi, Bo; Huang, Darong; Wan, Shaohua; Hu, Yu; Choo, Kim-Kwang Raymond
Highlights: We drew the lattice-based cryptographic primitive called NTRU into OT implementation for the first time, which assured the high computational performance and post-quantum property of our scheme. Moreover, since the parameters used in NTRU are technically configured, our protocol is scalable to some extent. According to the IND-CCA2 model, we argued that the fastest oblivious transfer protocol known today [25] is fragile under active adaptive attack. We also found that this protocol is not semantic secure under decisional Diffie-Hellman assumption over the bilinear cyclic group. Contrarily, the above security flaws are eliminated in our scheme as proved under universal composability frame. Our scheme is more applicable to heterogeneous and distributed environments thanks to the reusability of encoded data set. In addition, both the computation and communication performances of our protocol are preferable than that of Chou's scheme. The experiment results also imply that our protocol is adaptive to resource-constrained equipment. Abstract: Security is a key concern in any IoT deployment, particularly if we have to take into consideration future attacks facilitated by the use of quantum computers. Therefore, in this paper, we present a post-quantum lightweight 1-out- n oblivious transfer (OT) protocol, based on the NTRU cryptographic primitive. Compared to the OT scheme proposed by Chou and Orlandi in LATINCRYPT 2015, our protocol is more suitable for deployment in heterogeneous and distributed environment, due to the reusability of encoded data set. Findings from the performance evaluation indicate that the proposed protocol outperforms that of Chou and Orlandi [13] protocol, in terms of computation and communication costs.